Pea Peptide Supplementation in Conjunction With Resistance Exercise Promotes Gains in Muscle Mass and Strength - Jia, Shaohui; Wu, Qiming; Wang, Shue; Kan, Juntao; Zhang, Zhao; Zhang, Xiping; Zhang, Xuejun; Li, Jie; Xu, Wenhan; Du, Jun; Wei, Wei (Frontiers in Nutrition, 2022)
It is generally considered that protein supplementation and resistance exercise significantly increase muscle mass and muscle growth.. As the hydrolysis products of proteins, peptides may play the crucial role on muscle growth. In the present study, male rats were oral administrated 0.4 g/kg body weight of pea peptide combined with 8 weeks of moderate intensity resistance exercise training. After treatment, the body gains, upper limb grip, muscle thickness and wet weight of biceps brachii were tested, the cross-sectional area of biceps brachii muscle fiber and the types of muscle fibers were determined by HE staining, immunofluorescence staining and lactate dehydrogenase activity, respectively. Western blot analysis was used to investigate the level of growth signaling pathway related proteins. The results showed that pea peptide supplementation combined with resistance exercise training significantly increased body weight, upper limb grip, muscle thickness, wet weight of biceps brachii and cross-sectional area of muscle fiber. Meanwhile, pea peptide supplementation obviously elevated the ratio of fast-twitch fiber (type II) and the expression of muscle growth signaling pathway related proteins. In addition, the PP2 oligopeptide in pea peptide with the amino acid sequence of LDLPVL induced a more significant promotion on C2C12 cell growth than other oligopeptides.